Bis(dimethylammonium) 2,5-dihydroxybenzene-1,4-disulfonate - Shan Gao; Seik Weng Ng (Acta Crystallographica Section E, 2012)
In the crystal of the title salt, 2C2H8N+·C6H4O8S22−, the anion lies on a center of inversion. The dimethylammonium cation forms one N—H...O hydrogen bond and another bifurcated N—H...O hydrogen bond. The hydroxy group links with the sulfonyl group via an intermolecular O—H...O hydrogen bond. These N—H...O and O—H...O hydrogen bonds generate a three-dimensional network.